NOCTURNAL AND DIURNAL TRENDS OF SURFACE URBAN HEAT ISLAND INTENSITY: A SEASONAL VARIABILITY ANALYSIS FOR SMART URBAN PLANNING - K. Dutta; D. Basu; S. Agrawal (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2019)
Land management in the limited environment of city regions with immense population pressure is a challenging task. To achieve the goal of sustainable smart cities, reliable spatial information needs to be incorporated in land governance policies. In this study, Landsat 8 satellite bands were processed to derive the land use characteristics which are causing the development of urban heat islands at certain locations. To assess the prolonged effects of heat-trapping in cities, night time temperature data was obtained through in-situ data collection with error within 1 °C. Much higher intensity of urban heat island was observed during the night. The maximum increase of 1.67 °C was noted from day to night temperature for the same heat island. Seasonal analysis between winter and summer months was also carried out. The results suggested that for both day and night summer months produced more critical heat islands with maximum intensity up to 3.48 °C; while in winter the heat island intensity did not exceed 2.18 °C. Through comparative analysis between two cities with varying extent, urbanization and population pressure, it was observed that the maximum intensity of day time temperature was greater in a bigger city and heat islands were less fragmented. Heat islands covered an area of 10.39 km2 over Prayagraj and 28.29 km2 area of Kolkata. The temperature patterns obtained during day and night were statistically validated with the index of impervious surface area, at the significance level of α0.05.